1993
DOI: 10.1002/dvg.1020140104
|View full text |Cite
|
Sign up to set email alerts
|

The independent stage‐specific expression of the 18‐kDa heat shock protein genes during microsporogenesis in Zea mays L

Abstract: The small (18-kDa) heat shock proteins (hsps) of maize are encoded by a complex multigene family. In a previous report, we described the genetic information from cDNAs encoding two different members of the family. In this communication, we report the isolation and characterization of cDNA and genomic clones encoding information for a third member of this hsp family (c/gMHSP18-1). DNA fragments containing nucleotide sequences common to, or specific for, each of these characterized 18-kDa genes were prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Our data at the protein level extend those of Dietrich et al (1991) and Atkinson et al (1993) who reported developmental regulation of specific HSP18 mRNAs during maize male development and particularly their accumulation in anthers near meiosis. In addition, our data indicate that most of the members of the maize microspore lowmolecular-mass HSP family are likely to be very stable, since they were present at the control temperature on immunoblots and were not detected on 28°C fluorograms.…”
Section: Expression Of Microspore Hsps At Non-heat-shock Temperaturesupporting
confidence: 89%
See 1 more Smart Citation
“…Our data at the protein level extend those of Dietrich et al (1991) and Atkinson et al (1993) who reported developmental regulation of specific HSP18 mRNAs during maize male development and particularly their accumulation in anthers near meiosis. In addition, our data indicate that most of the members of the maize microspore lowmolecular-mass HSP family are likely to be very stable, since they were present at the control temperature on immunoblots and were not detected on 28°C fluorograms.…”
Section: Expression Of Microspore Hsps At Non-heat-shock Temperaturesupporting
confidence: 89%
“…During maize male development, such HSP gene expression has been reported at meiosis (Dietrich et al, 1991;Atkinson et al, 1993;Bouchard et al, 1993;Marrs et al, 1993). As with meiosis, first pollen mitosis is a key event of pollen formation (McCormick, 1993;Eady et al, 1995).…”
mentioning
confidence: 99%
“…Their putative roles range from protecting the cell from damaged protein aggregates accumulated during stress (Lee et al 1997;Mogk et al 2003) to potential functions in pollen and seed development (Waters et al 1996;Wehmeyer et al 1996;Lubaretz and zur Nieden 2002). Expression of plant sHsp genes, well known to be basically regulated on the transcriptional level, was previously found during hs and some other stressful conditions in most vegetative tissues as well as during maturation of pollen and seeds (Almoguera and Jordano 1992;Atkinson et al 1993;Kobayashi et al 1994;Prändl et al 1995;Zarsky et al 1995;Coca et al 1996;Wehmeyer et al 1996;Carranco et al 1997). This typical expression behavior was only observed for two of the newly defined sHsps (Hsp18.5-CIV and Hsp26.5-MII).…”
Section: Regulation Of Shsp Expressionmentioning
confidence: 99%
“…Similar observations in plants are still scarce [reviews in 4,5], although there are examples showing expression of specific HSP genes during pollen development [6,7], fungal sporulation [8], and in zygotic [9][10][11] as well as somatic embryogenesis [12,13]. Some of these examples include LMW HSP genes [6,7,10,12,13], but in most cases only mRNA accumulation or in vitro translation data have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Some of these examples include LMW HSP genes [6,7,10,12,13], but in most cases only mRNA accumulation or in vitro translation data have been reported. Use of antibodies against cytoplasmic class I LMW HSPs [ 14] has confirmed in vivo accumulation of these proteins in mature seeds from field-grown plants [ 15].…”
Section: Introductionmentioning
confidence: 99%